Chloroplast genome sequencing and divergence analysis of 18 Pyrus species: insights into intron length polymorphisms and evolutionary processes - Kim, Jung Sun; Chung, Hoyong; Park, Bohyeon; Veerappan, Karpagam; Kim, Yoon-Kyung (Frontiers in Genetics, 2024)
Pears constitute an essential temperate crop and are primarily produced through interspecific hybridization owing to self-incompatibility that complicates their breeding history. To address this, we sequenced the complete chloroplast (cp) genomes of 18 Pyrus and one Malus species using the Illumina HiSeq4000 platform. The cp genomes ranged from 159,885 bp to 160,153 bp and exhibited a conserved circular DNA structure with an average GC content of 36.5%. Each cp genome contained 127 genes, including 83 protein-coding, 36 tRNA, and 8 rRNA genes. Divergence analysis with mVISTA showed high conservation in the coding regions and notable variations in the non-coding regions. All species shared 17 intron-containing genes, with ycf3 and clpP each having two introns. Five intron-containing genes (ndhB, rpl2, rps12, trnA-UGC, and trnE-UUC) were located in the inverted repeat regions, while trnL-UAA was located in the large single-copy region, with conserved intron lengths across Pomoideae. We identified polymorphic intron sequences in the rpl22, petB, clpP, ndhA, and rps16 genes and designed primers for these regions. Notably, the two Pyrus ussuriensis accessions Doonggeullebae and Cheongdangrori showed intron-length polymorphisms despite being classified as the same species. Phylogenetic analysis of the cp genome sequences revealed two major clusters, indicating distinct maternal lineages and evolutionary origins. This study underscores the importance of cp gene polymorphisms in P. fauriei, P. calleryana, P. ussuriensis, and P. pyrifolia, providing valuable insights into Pyrus evolution as well as aiding in the conservation and breeding of pear germplasm.